CORRELATION BETWEEN ANXIETY LEVEL AND SELF DIRECTED LEARNING READINESS (SDLR) WITH STUDENT PEFORMANCE IN PROBLEM BASED LEARNING (PBL) - Nita Safitri; Uswatun Khasanah; Ruri Eka Maryam Mulyaningsih (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: The pattern of medical education in Indonesia has changed from teacher-centered learning to student-centered learning. This change has an impact on methods, learning activities, and learning achievements of medical students. Problem Based Learning (PBL) is one of the main learning methods used in the faculty of medicine. PBL is a learning method that requires students to play an active role and facilitate collaborative learning. Due to the change of learning method, new medical students experience a lot of stress from in doing Problem Based Learning such as anxiety and may affect their PBL results as can be evaluated using Self-Directed Learning Readiness (SDLR). There are very few studies found to date investigating this phenomenon.Aims: This research aims to see the correlation between anxiety level and SDLR with student’s performance participating in first-year PBL in the Musculoskeletal and Locomotory System block in the faculty of medicine Universitas Swadaya Gunung Jati Cirebon.Methods: This is a cross-sectional observational study with total sampling. The samples were recruited from 167 first-year 2018 intake students of the faculty of medicine Universitas Swadaya Gunung Jati. Zung Self Rating Anxiety Scale questionnaire is used to measure anxiety levels and the SDLR questionnaire is used to measure Self Directed Learning Readiness (SDLR).Results: The Spearman test showed a medium negative correlation value of -0.49 (p>0.05) for the level of anxiety. It means that there is no significant effect of anxiety on the PBL performance. In addition, it shows a weak positive correlation value of 0.196 (p <0.05) for SDLR (self-directed learning readiness) showing a significant influence on PBL performance.Conclusions: The level of anxiety does not significantly influence PBL performance while SDLR has a significant effect on PBL performance.